A Research on the Political Thoughts of Pandit Jawaharlal Nehru: Examining Nehru's Political Philosophy and Contributions to Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nehru imparted a socialistic vision to the Indian development. Nehru adopted Marxism in the 1930s as a tool for understanding society, social development and the national movement itself He disagreed, on one basic question at lease after 1936, with the con¬temporary Marxist position. He used Marxism to understand Indian social development even after 1947. It was diluted over the years. He did not see nationalism as inherently a ‘bourgeoisie’ ideology, though he saw the national movement being dominated at the time by the middle classes. He felt, in the colonial and post-colonial situation that nationalism could be and had to be, articulated and integrated with socialist ideology. Nehru kept his commitment to nationalism, national unity and national independence after 1947. He safeguarded the political independence won in 1947, and he laid the foundations of a democratic and civilian polity, and also carried forward the process of the making of the Indian nation. There is hardly any doubt that Nehru was successful in laying the foundations of an independent economy, otherwise known as mixed economy, through a capitalist economy. Elections, civil liberties and freedom to organize and grass root democracy through institutions such as Panchayat Raj would enable the people to mobilize them¬selves to exert pressure from below, compelling the political party in power either to make the necessary changes or get swept away. Soviet Union was the only major power to allow India to develop independent capabilities in many spheres of heavy industry, engineering and cutting edge technologies. India’s combination of internal political freedom, economic and political independence throughout its existence can be favorably compared with many client states of the United States and the Soviet Union. Democracy was, in his conception, linked to the unity of the country. Democracy would also guarantee that the process of nation-building would be accomplished through social justice and equity. People would use the democratic system to generate political progress to achieve its social objectives. For him, political equality implies universal adult suffrage, organization of a strong democratic polity, political parties, legislatures with a true representative character, public opinion, freedom of the press, electoral reforms, political rights, constitutional safeguards, constitutional methods, faith in constitutional process, legitimization of the constitutional system and lastly secularism. For him, social equality aims for the removal of social discrimination on the grounds of race, sex, gender and natural incapacities. It means equal opportunities to lead a happy life in the social sphere. It also includes elimination of poverty, social stigma and inhuman activities extension of voting rights to the underprivileged, equal participation without gender inequality, in the political process and receiving equal benefits as the members of a society.